Heavy Metal and Nutritional Profiles of Sargassum crassifolium Flour from Tomini Bay - Renofandi A. Dien; Faiza A. Dali; Shindy Hamidah Manteu (Information Technology and Science (ITScience), 2026)
Sargassum crassifolium is a nutrient-dense brown macroalga with significant potential as a functional food ingredient, yet its utility is often constrained by its capacity to bioaccumulate contaminants in anthropogenically stressed coastal environments. This study evaluates the proximate composition, macro-mineral profiles, and heavy metal concentrations of S. crassifolium flour harvested from Kaisomaru, Tomini Bay, to determine its safety and nutritional viability for industrial applications. Nutritional composition was analyzed using AOAC-standardized methods, while spectrophotometric techniques were employed to quantify essential minerals (Ca, Mg, Na, K, Fe) and toxic heavy metals (Cd and As). Results indicate that the seaweed is rich in dietary fiber and ash with low lipid content, confirming its status as a promising source of essential minerals, particularly calcium. However, the heavy metal assessment reveals a critical safety breach regarding arsenic (As) concentrations, which consistently exceed maximum residue limits established by the Indonesian National Standard (SNI 2690:2015). This bioaccumulation is driven by the structural